1969
DOI: 10.1002/1097-0142(196906)23:6<1436::aid-cncr2820230627>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoid of meckel's diverticulum. Report of a case and review of the literature

Abstract: A patient with carcinoid of Meckel's diverticulum, and a review of the literature are presented. Thirty‐two of the patients were men and 8 were women. Their ages ranged from 12 to 80 years. Of the 37 in the 40 to 80 age group, 18 were in the age 50‐59 group. Carcinoid of Meckel's diverticulum was an unsuspected and primarily incidental finding at autopsy and surgery in 19 and 21 cases respectively. Gastrointestinal hemorrhage occurred in one patient from an ulcerated carcinoid. Five of the diverticula were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A number of reports in the literature describe NETs in a Meckel’s diverticulum that were discovered incidentally during an abdominal exploration for another indication or at autopsy[11,15,16,17]. A review of the literature by Nies et al[6] found that 64% of patients with NETs in a Meckel’s diverticulum were asymptomatic at the time of diagnosis, and 26% were found incidentally at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports in the literature describe NETs in a Meckel’s diverticulum that were discovered incidentally during an abdominal exploration for another indication or at autopsy[11,15,16,17]. A review of the literature by Nies et al[6] found that 64% of patients with NETs in a Meckel’s diverticulum were asymptomatic at the time of diagnosis, and 26% were found incidentally at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of EMPs varies depending on the study. In histological analysis at autopsy of patients with myeloma, Weitzner reported the incidence of extramedullary plasmacytoma ranging from 11 and 73% [2] . In autopsy studies, Hayes et al found microscopic disease in the liver, spleen, and lymph nodes in 70% of these patients, but reported that gross extramedullary plasmacytoma in other locations were much less common and rarely affected more than one anatomical site [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Isolated testicular plasmacytomas are rare entity. The mean age of diagnosis is 55 to 60 years, with a male to female ratio of two to one [1][2][3]. The diagnosis of EMP requires studies including complete and differential blood counts with peripheral smears, complete metabolic panel, serum protein electrophoresis with immunofixation of immunoglobulin, biopsy of the lesion, bone aspiration and biopsy, and metastatic bone survey by positron emission tomography (PET) with computed tomography (CT) or magnetic resonance imaging (MRI).…”
Section: Discussionmentioning
confidence: 99%
“…Like argentaffin-cell tumours of the appendix (Dawes et al, 1984), carcinoid tumours occurring in a Meckel's diverticulum are usually small, the majority measuring 1 cm or less in diameter (Weitzner, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoid tumours within a Meckel's diverticulum are seen four times more commonly in men than women (Weitzner, 1969;Jones et al, 1972). This sex distribution probably reflects the higher incidence of both Meckel's diverticulum (Yamaguchi et al, 1978) and small intestinal carcinoids (Godwin, 1975) …”
Section: Discussionmentioning
confidence: 99%